PENGARUH NILAI RELIGIUSITAS TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 10 LUBUK ALUNG - Rahmi Mulya; Sulaiman Sulaiman (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
This study aims to determine the effect of religious values ​​on student learning outcomes in Islamic Religious Education classes IV and V at SDN 10 Lubuk Alung. This type of research is a quantitative research using associative research methods. The population in this study were grades IV and V at SDN 10 Lubuk Alung. The sample in this study was taken from the entire population of 31 respondents. The data collection technique uses a questionnaire and documentation. Data analysis used simple linear regression analysis, with religiosity values ​​as the independent variable and student learning outcomes as the dependent variable. The results of the study indicate that the values ​​of religiosity partially have a positive and significant effect on student learning outcomes in learning Islamic Religious Education.